2008
DOI: 10.1111/j.1467-7652.2008.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered native pathways for high kaempferol and caffeoylquinate production in potato

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 67 publications
(59 reference statements)
0
65
1
Order By: Relevance
“…Vertical bars indicate the standard deviation of three biological replicates. Asterisks indicate a significant difference at the P \ 0.05 level Plant Cell Tiss Organ Cult increased expression of phenylpropanoid synthesis related genes (Rommens et al 2008). We further analyzed whether the increased caffeoylquinic acid contents in transgenic plants overexpressing SbMYB8 was due to the changed expression of flavonoid biosynthesis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical bars indicate the standard deviation of three biological replicates. Asterisks indicate a significant difference at the P \ 0.05 level Plant Cell Tiss Organ Cult increased expression of phenylpropanoid synthesis related genes (Rommens et al 2008). We further analyzed whether the increased caffeoylquinic acid contents in transgenic plants overexpressing SbMYB8 was due to the changed expression of flavonoid biosynthesis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, further biochemical analysis will be necessary to determine if this overall modulation of the phenylpropanoid pathway is directed primarily toward an increased production of scopoletin and its glucosylated derivative scopolin that accumulate during PPD (Wheatley and Schwabe, 1985;Buschmann et al, 2000b). Previous studies demonstrated the antioxidant activity of free scopoletin as well as the phenylpropanoid caffeoyl quinate (chlorogenic acid), which is produced by p-coumaroyl shikimate/quinate 39-hydroxylase (Chong et al, 1999;Niggeweg et al, 2004;Rommens et al, 2008). Thus, phenylpropanoid pathway modulation might also reflect a response to ROS production during PPD (Reilly et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Neochlorogenic and cryptochlorogenic acids were quantitated as chlorogenic acid equivalents (Shakya and Navarre 2006). Flavonols were determined as previously described and kaempferol-rutinose was expressed as rutin equivalents (Rommens et al 2008). Authentic standards for kaempferol-rutinose were not available, so tentative identification was based on the uv spectrum and a pseudomolecular ion of m/z 593 (M-H) − and a MS 2 product ion of m/z 285 (M-H-rutinose) − .…”
Section: Hplc Analysismentioning
confidence: 99%
“…Furthermore, some wild species exhibit less enzymatic browning despite higher phenolic concentrations than S. tuberosum cultivars (Sim et al 1997). Transgenic approaches have shown that it is possible to markedly increase tuber phenolic acids, anthocyanins and flavonols (Lukaszewicz et al 2004;Rommens et al 2008). Chlorogenic acid is bioavailable in humans (Monteiro et al 2007), may decrease the risk of type two diabetes (Legrand and Scheen 2007) and slow the release of glucose into the bloodstream (Bassoli et al 2008), which could be relevant for lowering the glycemic index value of potatoes.…”
Section: Introductionmentioning
confidence: 97%